Compliance e boas práticas empresariais frente à função social da empresa - Schroeder, Simone Aparecida Altruda (2020)
The present study focuses on the importance of Compliance and good business practices as as a means to achieve the constitutional objective of the social function, using tools since the implementation and constant monitoring with the scope of maintaining ethical and transparent behavior in the face of society. The global movement of social involvement favors of the private sector in an activity in this sense, is aligned with social welfare and the behavior of corporate citizenship. To start with the hypothetical-deductive method, the study is based on bibliographic research, including websites of World Wide Web; documentary consultating for relevant legislation and legislation to the subject; and field, based on questionnaires and interviews of qualitative data with companies and professionals in the area. As a result, it was possible to check the theme of relevance related to compliance and to such tools as relevant parts of this work, which has been the object attention special in private sector, inside and outside the country, which increasingly improve actions directed to the social commitment.